Narratives, Nerdfighters, and New Media - Burek Pierce, Jennifer (Book collections on Project MUSE., 2020)
For decades, we've been warned that video killed the radio star, and, more recently, that social media has replaced reading. Nerdfighteria, a first-of-its-kind online literary community with nearly three million members, challenges these assumptions. It is the brainchild of brothers Hank and John Green, who provide literary themed programming on their website and YouTube channel, including video clips from John, a best-selling author most famous for his young adult book, The Fault in Our Stars. These clips not only give fans personal insights into his works and the writing process writ large, they also provide unique access to the author, inspiring fans to create their own fan art and make connections with one another. In the twenty-first century, reading and watching videos are related activities that allow people to engage with authors and other readers. Whether they turn to The Fault in Our Stars or titles by lesser-known authors, Nerdfighters are readers. Incorporating thousands of testimonials about what they read and why, Jennifer Burek Pierce not only sheds light on this particular online community, she also reveals what it tells us about the changing nature of reading in the digital age. In Nerdfighteria, we find a community who shows us that being online doesn't mean disinterest in books.